Isolasi Bakteri Selulolitik dari Limbah Kulit Pisang - Sukmawati Sukmawati (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2018)
Cellulose can be found in whole parts of plants. Cellulose can be degraded by cellulose enzyme. Cellulose enzyme is produced by cellulolytic bacteria which has ability to degrade the cellulose and fiber. Cellulose enzyme is extremely important in industry sector. This research aims to isolate the cellulosic bacteria of peel waste of Banana in Sorong, West Papua. This research used isolation and purification method by using 1 gram of Banana peel. It was isolated in CMC (Carboxymethyl cellulose) selective media and morphology characteristic test using 400X-1000X microscope and zone index test. The result showed that the cellulosic ability was found in isolate B with pure zone index 3mm and the smallest pure zone index was in isolate H with pure zone index 0,8 mm. while, the isolate C had zone pure index 1,5 mm, isolate D 1,625 mm, isolate E 1 mm, isolate F 0,714mm, and isolate G 2 mm.